A virtual roundtable on Iser’s legacy Part I: conversation with Gerald Prince (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
In this article you find the first part of a roundtable on Wolfgang’s Iser legacy with Gerald Prince, Mark Freeman, Marco Caracciolo and Federico Bertoni. In Part I we discuss with Prof. Gerald Prince the influence of Iser’s aesthetic response theory on past and current reader oriented approaches, as well as Iser’s last insights on literary anthropology and the role of literary theory.